Opportunities from the RCEP: ASEAN Perspectives on Economic and Non-Economic Gains Through Regional Integration - Elisabeth Kristanti; Evi Fitriani (Green Publisher Indonesia, 2025)
The Regional Comprehensive Economic Partnership (RCEP) represents the world's largest regional trade agreement, encompassing ASEAN, China, Japan, South Korea, Australia, and New Zealand, covering 30% of the global economy. This study analyzes opportunities from the RCEP agreement for ASEAN's economic and non-economic gains through the lens of neoliberal institutionalism and international cooperation theory. The research methodology compares the RCEP agreement with existing relevant agreements, analyzes trade data and trends between RCEP members, and identifies opportunities based on regional issues. Methods include comparative analysis of trade agreements, examination of trade in goods and services data, and evaluation of regional cooperation frameworks. Results indicate that ASEAN can leverage e-commerce growth to strengthen extra-regional integration, gain strategic positions in production chains, and increase trade-in services value through small and medium enterprise development. For non-economic aspects, enhanced international trade within RCEP can help maintain regional stability and address data security challenges. The study finds no evidence of state centrality requirements in RCEP, contrary to common arguments about regional leadership dynamics. The RCEP framework provides ASEAN with opportunities to enhance both economic competitiveness and political security through multilateral cooperation without requiring hierarchical leadership structures.